Cancer and embryo expression protein 65 promotes cancer cell growth and metastasis - JIN, GENGLIN (Oncol Lett, 2015)
Cancer and embryo expression protein 65 (CEP65) is a centrosomal protein that is expressed at relatively high levels in embryonic tissue and different cancerous tissues, but its role in tumorigenesis remains unknown. In the present study, CEP65 was stably expressed in AGS gastric cancer cells. CEP65 was found to promote cell growth in the MTT assay and to enhance cell migration and invasion in Transwell chamber assays. To validate results from the in vitro experiments, CEP65 was stably expressed in BICR-H1 breast cancer cells through adenovirus-mediated transduction. By inoculating BICR-H1 cells on chick chorioallantoic membrane (CAM), it was found that CEP65 promotes cell growth on the CAM and increases cell metastasis to the lungs of the chicken. By utilizing a xenograft severe combined immunodeficiency mouse model, CEP65 was also found to accelerate BICR-H1 cell growth and metastasis to the lungs. Furthermore, it was shown that CEP65 increases matrix metalloproteinase (MMP)2 activity in zymographic assays, however, microarray screening and reverse transcription polymerase chain reaction validation revealed that CEP65 had no effect on the expression levels of MMP2 or MMP9, but decreased the expression levels of metastasis-associated genes, TIMP2, RAP and VTN. Taken together, the results of the present study demonstrated the oncogenic function of CEP65 in promoting cancer cell growth and metastasis.